Peran Teknologi Di Dunia Pendidikan Dalam Meningkatkan Kualitas Pembelajaran - Soviatur Rahmah; Elya Soviana; Fitriyana Fitriyana (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
In the current era of globalization, technological developments are taking place very rapidly and have a significant influence on the world of education. The ongoing development of the era requires the world of education to continue to adapt in order to adjust to technological advances, especially in improving the quality of education through the application of technology and information in the learning process. This study aims to highlight the importance of the role of technology in improving the quality of learning in the world of education. The method used in this study is a literature study, by collecting data from various sources, especially scientific journals that are relevant to the topic of discussion. The results of the study show that technology has a crucial role in education, especially in facilitating access to information and data. Thus, technology is very helpful in the learning process, especially in the modern era which is marked by rapid technological advances.